Endovascular Repair of the Blunt Injury to Persistent Sciatic Artery in Case of Pelvic Fracture - Mayzler, Olga; Leytzin, Anatoly; Ginzburg, Victor; Greenberg, George (Journal of Endovascular Resuscitation and Trauma Management, 2019)
Background: Endovascular embolization has become a preferred treatment in the management of retroperitoneal bleeding due to pelvic injuries. These techniques have spread across most trauma centers as minimally invasive management of one of the most dreadful conditions in trauma. Methods: We present a patient with persistent sciatic artery who arrived at our facility with blunt pelvic trauma suffering from retroperitoneal bleeding. Timely recognition of this anomaly led to the preservation of the vital artery and prevention of ischemic complication. Conclusions: Although embolization of the bleeding has become a routine procedure in most busy trauma centers, precise imaging, recognition of significant anatomic variants and careful intervention planning are essential in preventing substantial complications.